A Comparison of DNA Mutation and Copy Number Profiles of Primary Breast Cancers and Paired Brain Metastases for Identifying Clinically Relevant Genetic Alterations in Brain Metastases - Tyran, Marguerite (Cancers (Basel), 2019)
Improving the systemic treatment of brain metastases (BM) in primary breast cancer (PBC) is impaired by the lack of genomic characterization of BM. To estimate the concordance of DNA copy-number-alterations (CNAs), mutations, and actionable genetic alterations (AGAs) between paired samples, we performed whole-genome array-comparative-genomic-hybridization, and targeted-next-generation-sequencing on 14 clinical PBC–BM pairs. We found more CNAs, more mutations, and higher tumor mutational burden, and more AGAs in BM than in PBC; 92% of the pairs harbored at least one AGA in the BM not observed in the paired PBC. This concerned various therapeutic classes, including tyrosine-kinase-receptor-inhibitors, phosphatidylinositol 3-kinase/AKT/ mammalian Target of Rapamycin (PI3K/AKT/MTOR)-inhibitors, poly ADP ribose polymerase (PARP)-inhibitors, or cyclin-dependent kinase (CDK)-inhibitors. With regards to the PARP-inhibitors, the homologous recombination defect score was positive in 79% of BM, compared to 43% of PBC, discordant in 7 out of 14 pairs, and positive in the BM in 5 out of 14 cases. CDK-inhibitors were associated with the largest percentage of discordant AGA appearing in the BM. When considering the AGA with the highest clinical-evidence level, for each sample, 50% of the pairs harbored an AGA in the BM not detected or not retained from the analysis of the paired PBC. Thus, the profiling of BM provided a more reliable opportunity, than that of PBC, for diagnostic decision-making based on genomic analysis. Patients with BM deserve an investigation of several targeted therapies.